Comparison of the effect of light-cure and dual-cure bondings on regional bond strength of fiber reinforced posts to root canal - Aminsalehi E.; Emami Ardestani S. (Tehran University of Medical Sciences, 2008)
Background and Aim: The use of fiber reinforced posts in endodontically treated teeth has become increasingly common. But their retention in root canals must be considered seriously. The aim of this study was to evaluate the effect of light-cure and dual-cure bondings on regional bond strength of a fiber composite post.Materials and Methods: In this experimental in vitro study, 20 endodontically treated teeth were randomly divided into two groups. In the first group, a dual-cure bonding (Scotchbond Multi-Purpose Plus, 3M ESPE/USA) [SBMP] was used and in the other group, a light-cure bonding (Single Bond, 3M ESPE/USA) [SB] was applied according to the manufacturer's instructions. A dual-cure resin cement (Rely X ARC, 3M ESPE/USA) was used to cement the post (Glassix, Harald Nordin SA,Switzerland). Coronal 8mm of cemented posts were sectioned in equal thirds using a 0.1mm diamond disc. Each slice was polished by a soft and wet abrasive paper in order to get a 2mm thickness. Loading was performed by a testing machine (Zwick/Germany) at a speed of 1mm/min until the post was dislodged. Data were analyzed using one-sample Kolmogorov-Smirnov, T and ANOVA tests with P<0.05 as the level of significance.Results: There was a significant difference between the two adhesive systems in the middle third of the canal block with higher bond strength in SBMP group (p=0.02). In SB group the bond strength of the cervical region was higher than the middle and apical thirds (p<0.05). In SBMP group, there was no statistically difference between bond strength of the three regions (p=0.117).Conclusion: Based on the results of this study, dual-cure bonding could be recommended for composite post cementation into root canals, because its bond strength was more uniform in different regions of root and greater in the middle and third regions.